The influence on peroneal reaction time after five days of ankle taping - Esteves, José Manuel (2008)
Objectives: To study the influence of ankle taping on proprioception and active mechanism of joint protection by indirectly measuring of the proprioception. Methods: The sample was constituted by 32 healthy subjects randomly assigned to either an experimental group (n=17) or a control group (n=15). Subjects had a mean age of 19 years (min=17-max=24), a mean height of 1,67 m (min=1,48-mix=1,80) and a mean weight of 62,5 kg (min=47,5- max=80,5). The experimental group subjects wore an ankle tape for 5 days. No intervention was done on the control group. Several measurements of the peroneal reaction time (PRT) were done before tape immobilization and after removing it. Measurements were done with a trapdoor and surface EMG. The PRT was calculated with a specific computer algorithm. Results: The wearing of ankle tape during five days did not influence the peroneal reaction time (p>0,05). Conclusions: It seems the ankle tape does not influence the active mechanism of joint protection of healthy subjects, however the decision to administer it should be thoughtful.